INCREASED DISSOLUTION RATE OF ACECLOFENAC BY FORMATION OF MULTICOMPONENT CRYSTALS WITH L-GLUTAMINE - JESSICA, ADHITYA; YASA, SIRLY WAHYUNI N.; ZAINI, ERIZAL; FITRIANI, LILI (International Journal of Applied Pharmaceutics, 2024)
Objective: The objectives of this research were to improve the solubility as well as the rate of dissolution of aceclofenac (ACF) through the formation of multicomponent crystals (MCC) with L-glutamine (LGLN) as a coformer and following the liquid-assisted grinding (LAG) technique. Methods: MCC of ACF and LGLN was formed by Liquid Assisted Grinding (LAG) technique. Powder X-ray Diffractometer (PXRD), Differential Scanning Calorimeter (DSC), Fourier Transform Infrared (FT-IR) spectrometer, Particle Size Analyzer (PSA), and Scanning Electron Microscope (SEM) were used for MCC characterization. Solubility and dissolution test were determined using ultraviolet-visible (Uv-Vis( spectrophotometer. Results: The results showed a decrease in the diffraction peak intensity, melting point, and enthalpy of fusion. FT-IR analysis showed a non-significant wavenumber shift compared to intact components. These characterizations showed that MCC formed a eutectic mixture. SEM and particle size analysis showed a homogeneous particle rod shape and decreased particle size. ACF's solubility in MCC increased 2.21 times more than intact form. MCC's dissolution rate increased by 5.34 times and 5.56 times, respectively, after 60 min in phosphate buffer pH 6.8 and CO2-free distilled water. Conclusion: The formation of MCC of ACF and LGLN considerably enhances ACF's solubility and dissolution rate.